Donor-site local anaesthetic infusion catheter as an opioid-sparing agent in free flap reconstruction of the head and neck: a valuable adjunct to an enhanced recovery protocol. Issue 2 (February 2022) - Henry, C.J.; Barry, C.P.
Abstract: This paper presents the results of a retrospective case-controlled cohort study to investigate the effectiveness of a donor-site local anaesthetic infusion protocol to reduce opioid requirements, length of intensive therapy unit (ITU) stay, and incidence of postoperative delirium. Adult free flap head and neck patients were identified from a prospective database (n = 86). There was a significant reduction in mean opioid requirements (p < 0.001). Postoperative delirium was observed in 12 of 35 patients before introduction of the protocol, and in 10 of 51 patients after its introduction (p = 0.139). Donor-site local anaesthetic infusion reduces opioid requirements for patients undergoing head and neck free flap reconstruction, and is a valuable adjunct to an enhanced recovery protocol.